2019
DOI: 10.1038/s41467-018-08169-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of MXenes’ electronic properties through termination and intercalation

Abstract: MXenes are an emerging family of highly-conductive 2D materials which have demonstrated state-of-the-art performance in electromagnetic interference shielding, chemical sensing, and energy storage. To further improve performance, there is a need to increase MXenes’ electronic conductivity. Tailoring the MXene surface chemistry could achieve this goal, as density functional theory predicts that surface terminations strongly influence MXenes' Fermi level density of states and thereby MXenes’ electronic conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
809
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 934 publications
(850 citation statements)
references
References 77 publications
(128 reference statements)
33
809
7
1
Order By: Relevance
“…SEM is used widely to observe the sheet‐like structure of MXenes . Here, we conducted SEM on the cross‐section of AEAPTMS‐Ti 3 C 2 T x and found that the layered structure of the pristine MXene stays intact even after the functionalization reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…SEM is used widely to observe the sheet‐like structure of MXenes . Here, we conducted SEM on the cross‐section of AEAPTMS‐Ti 3 C 2 T x and found that the layered structure of the pristine MXene stays intact even after the functionalization reaction.…”
Section: Resultsmentioning
confidence: 98%
“…To evaluate the different types and strengths of bonding between AEAPTMS and Ti 3 C 2 T x , TGA and MS of pristine and AEAPTMS‐Ti 3 C 2 T x were performed and presented in Figure . The thermogram of pristine MXene indicates the dehydration of the material from 25 °C up to ≈300 °C, which correlates to the water ( m / z = 18) curve in the MS shown in Figure 4B. High temperatures are required to dehydrate free‐standing MXene films due to the intercalation of water in small interlayer spacing of ≈10 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, there are four deconvoluted peaks corresponding to the surface functional groups including –OH, –O, and trapped water molecules, which are inevitably formed during the chemical etching of parental Ti 3 AlC 2 . After thermal treatment, peak intensities for Ti‐OH and Ti‐H 2 O are significantly reduced, confirming that reduction in gallery spacing between MXene layers upon thermal treatment is not due to the phase transformation to TiO 2 or oxidation of MXene, but due to the removal of intercalants, such as absorbed H 2 O and partial loss of surface terminations such as –OH, –F, and –O …”
mentioning
confidence: 75%
“…[15,16,26] Therefore, the Ti 3 C 2 T x /BST interface in the composite can be deemed as a typical metal-semiconductor contact, which could lead to the formation of interface potential (V) due to the difference of work function for the two materials. [15,16,26] Therefore, the Ti 3 C 2 T x /BST interface in the composite can be deemed as a typical metal-semiconductor contact, which could lead to the formation of interface potential (V) due to the difference of work function for the two materials.…”
Section: Thermoelectric Transport Propertiesmentioning
confidence: 99%